Förster-type nonradiative energy transfer for assemblies of arrayed nanostructures : confinement dimension vs stacking dimension - Hernández-Martínez, Pedro Ludwig (2015)
Förster-type nonradiative energy transfer (NRET) provides us with the ability to transfer excitation energy between proximal nanostructures with high efficiency under certain conditions. Nevertheless, the well-known Förster theory was developed for the case of a single donor (e.g., a molecule, a dye) together with single acceptor. There is no complete understanding for the cases when the donors and the acceptors are assembled in nanostructure arrays, though there are special cases previously studied. Thus, a comprehensive theory that models Förster-type NRET for assembled nanostructure arrays is required. Here, we report a theoretical framework of generalized theory for the Förster-type NRET with mixed dimensionality in arrays. These include combinations of arrayed nanostructures made of nanoparticles (NPs) and nanowires (NWs) assemblies in one-dimension (1D), two-dimension (2D), and three-dimension (3D) completing the framework for the transfer rates in all possible combinations of different confinement geometries and assembly architectures, we obtain a unified picture of NRET in assembled nanostructures arrays. We find that the generic NRET distance dependence is modified by arraying the nanostructures. For an acceptor NP the rate distance dependence changes from 6dγ−∝ to 5dγ−∝ when they are arranged in a 1D stack, and to 4dγ−∝ when in a 2D array, and to 3dγ−∝ when in a 3D array. Likewise, an acceptor NW changes its distance dependence from 5dγ−∝ to 4dγ−∝ when they are arranged in a 1D array and to 3dγ−∝ when in a 2D array. These finding shows that the numbers of dimensions across which nanostructures are stacked is equally critical as the confinement dimension of the nanostructure in determining the NRET kinetics.